The Case for the Safe Re-Opening of Student-Run Clinics during COVID-19 - Sarah Hopfer; Reese Miller; Olivia Neese; Sarah Swiezy (Journal of Student-Run Clinics, 2022)
Coronavirus disease 2019 (COVID-19) has presented a unique challenge to student-run free clinics (SRFCs), with many closing for several months and all needing to find ways to adapt to the new “normal” of the pandemic. While the prospect of new variants and higher surges continues to threaten our ability to keep SRFC doors open to serve the neediest patients among our community, we present here arguments from need, practicality, safety, and ethics that COVID-19 is the ideal time to maintain—and, even expand—the services SRFCs provide. With so many patients relying on SRFCs for their primary care and with the ability to use precautionary measures to safely see and treat patients, SRFCs should play a vital role in helping the overburdened healthcare system continue to function and provide needed care, despite the devastating impacts of COVID-19.